2017
DOI: 10.3390/ijerph14050550
|View full text |Cite
|
Sign up to set email alerts
|

Early Childhood Dental Caries, Mouth Pain, and Malnutrition in the Ecuadorian Amazon Region

Abstract: Malnutrition and dental caries in early childhood remain persistent and intertwined global health challenges, particularly for indigenous and geographically-remote populations. To examine the prevalence and associations between early childhood dental caries, parent-reported mouth pain and malnutrition in the Amazonian region of Ecuador, we conducted a cross-sectional study of the oral health and nutrition status of 1407 children from birth through age 6 in the “Alli Kiru” program (2011–2013). We used multivari… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 36 publications
1
34
0
2
Order By: Relevance
“…Across both age groups, severe caries by pufa+PUFA-an indication of deep dental infection, cavitation, and likelihood of dental pain-was associated with lower WAZ and BAZ, suggesting a risk for acute malnutrition, and in older children, severe caries by SiC was associated with lower HAZ, suggesting a risk for chronic malnutrition. This study adds to the growing literature from developing countries, demonstrating that severe dental caries may exacerbate the risk for childhood malnutrition, especially in early childhood [29,32,33,36]. The pathophysiologic mechanisms by which severe caries may contribute to malnutrition include chronic infection/inflammation and dental pain suppressing children's appetite and growth, loss of tooth structure inhibiting children's ability to chew nutritious foods, and increasing use of non-nutritious sweets to pacify children's chronic pain [32].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Across both age groups, severe caries by pufa+PUFA-an indication of deep dental infection, cavitation, and likelihood of dental pain-was associated with lower WAZ and BAZ, suggesting a risk for acute malnutrition, and in older children, severe caries by SiC was associated with lower HAZ, suggesting a risk for chronic malnutrition. This study adds to the growing literature from developing countries, demonstrating that severe dental caries may exacerbate the risk for childhood malnutrition, especially in early childhood [29,32,33,36]. The pathophysiologic mechanisms by which severe caries may contribute to malnutrition include chronic infection/inflammation and dental pain suppressing children's appetite and growth, loss of tooth structure inhibiting children's ability to chew nutritious foods, and increasing use of non-nutritious sweets to pacify children's chronic pain [32].…”
Section: Discussionmentioning
confidence: 83%
“…There have been mixed findings on the association between severe caries and nutritional status. Studies have demonstrated an association between severe caries and malnutrition in some low-income contexts, with caries contributing to mouth pain and chronic inflammation which disrupt normal eating, sleep, and growth [29][30][31][32][33]; associations with obesity in high-income contexts due to shared dietary risk factors [34,35]; and no associations in other studies [36]. There is limited research on these relationships in Nepali populations.…”
Section: Introductionmentioning
confidence: 99%
“…PLHIV are also at a higher risk for malnutrition [9], which may be exacerbated by dental caries. Studies suggest that caries of the primary and permanent dentitions is associated with early childhood malnutrition [12, 14] and increased likelihood of malnutrition [15] in the elderly respectively. PLHIV are now living longer due to ART, which means that chronic health issues like dental caries and oral health are increasingly important to manage well in HIV patients to prevent complications such as malnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, limited access to dental care leaves most ECC untreated, which can lead to widespread loss of tooth structure, chronic infection and inflammation, mouth pain, decreased appetite, disrupted sleep, and poor functioning and confidence in school, all of which interfere with children’s quality of life, growth, and development [9,10]. In low- and middle-income countries, studies have documented a significant association between ECC and malnutrition; a bidirectional relationship is postulated, where undernutrition predisposes a child to caries and caries predispose a child to undernutrition [11,12,13].…”
Section: Introductionmentioning
confidence: 99%